Human-oriented economy: goals and their contradictions - Nasyrova Svetlana (π-Economy, 2022)
Emphasis on a human through the satisfaction of his needs has always been the focus of the research of economic theorists. Numerous studies confirm the defining role of a human in the economy, which actualizes the issue of considering and identifying a human-oriented economy. The purpose of the study is to form a holistic view of the goals of a human-oriented economy, based on its immediate essence: the satisfaction of objectively necessary human needs. The study is based on the application of the “sequence of purposes” method of categorical-system methodology. Results of the study. First, the human-oriented economy is represented using three components of the categorical method: system (human-oriented economy), elements of the system (natural sphere, material sphere, service sector, social sphere, infosphere, digital sphere, creatosphere, cognitive sphere), its property (human-centered principle). Secondly, the goal settings of this economic system are disclosed, based on its hierarchical levels: goal, sub-goal, super-goal. Thirdly, the paper structures the contradictions that take place between the components of the economy, identified using the “sequence of purposes” method (goal, sub-goal, super-goal), as well as their interaction with the external environment. These contradictions include internal contradictions (contradictions between the sub-goals of a human-oriented economy, contradictions between the principle of combining the spheres of a human-oriented economy and the sub-goals of its individual spheres, contradictions between the sub-goals and the goal of a human-oriented economy, contradictions between a human-centric economy and the principle of combining spheres economy as parts into a whole) and external contradictions (contradictions between the principle of combining the spheres of a human-oriented economy and the external environment, contradictions between the subgoals of a human-oriented economy and the external environment, contradictions between a human-centric economy and the external environment). Fourthly, directions for resolving the identified contradictions and their consequences are determined. Finally, the contradictions that arise between the subsystems of a human-oriented economy are supplemented: horizontal (homogeneous and heterogeneous contradictions within one sphere) and vertical contradictions (conflicts arising within several spheres of the economy under consideration). The practical significance of the study is that the results obtained can be used in the development of mechanisms for managing the formation and development of a human-oriented economy.